Penyuluhan PENYULUHAN PENTINGNYA MENGENALKAN BAHASA INGGRIS PADA ANAK USIA DINI : - - Suprih Ambawani; Siti Saudah; Bernadetta Eko Putranti (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2024)
English language skills need to be mastered as means to prepare human resources to increase individual competitiveness in the global job market. English needs to be introduced from an early age, also known as the "golden age" where children have optimal ability to learn various languages. The purpose of this Community Service activity is 1) to provide parents with an overview of the importance of English language skills in the global era, and 2) to provide knowledge to mothers about the right method to introduce English to preschooler so that it can foster interest, motivation to learn English, and children's self-confidence and be able to compete in the global era. The Community Service activity was held on August 6, 2024 at 09.00-12.30 WIB. in the Multipurpose Room of Kapanewon Mlati, Sleman with participants from mothers in Kapanewon Mlati, Sleman, DIY. The method of implementing the activity was in the form of counseling through lectures accompanied by simulations of how to introduce English to preschoolers which were given through pictures, songs, movements, fairy tales, fun games and question and answer sessions. The results shower that the delivery of counseling material was able to improve mothers' understanding of the importance of introducing English, as well as being an appropriate and creative way to introduce English to preschooler which fosters interest and motivation to learn English, as well as forming independent learners who are able to compete in the global era. Therefore, it is hoped that parents will be able to foster interest in learning English from an early age which will have an impact on children's education and careers in the future.